Environmental management and potential valorization of wastes generated in passive treatments of fertilizer industry effluents. (May 2022) - Millán-Becerro, Ricardo; Macías, Francisco; Cánovas, Carlos R.; Pérez-López, Rafael; Fuentes-López, José M.
Abstract: A phosphogypsum stack located in SW Spain releases highly acidic and contaminated leachates to the surrounding estuarine environment. Column experiments, based on a mixture of an alkaline reagent (i.e., MgO or Ca(OH)2 ) dispersed in an inert matrix (dispersed alkaline substrate (DAS) technology), have shown high effectiveness for the treatment of phosphogypsum leachates. MgO-DAS and Ca(OH)2 -DAS treatment systems achieved near total removal of PO4, F, Fe, Zn, Al, Cr, Cd, U, and As, with initial reactive mass:volume of leachate treated ratios of 3.98 g/L and 6.35 g/L, respectively. The precipitation of phosphate (i.e., brushite, cattiite, fluorapatite, struvite and Mn3 Zn(PO4 )2 ·2H2 O) and sulfate (i.e., despujolsite and gypsum) minerals could control the solubility of contaminants during the treatments. Therefore, the hazardousness of these wastes must be accurately assessed in order to be properly managed, avoiding potential environmental impacts. For this purpose, two standardized leaching tests (EN-12457-2 from the European Union and TCLP from the United States) were performed. According to European Union (EN-12457-2) regulation, some wastes recovered from DAS treatments should be classified as hazardous wastes because of the high concentrations of SO4 or Sb that are leached. However, according to United States (US EPA-TCLP) legislation, all DAS wastes are designated as non-hazardous wastes. Moreover, the solids generated in the DAS systems could constitute a promising secondary source of calcite and/or P. This research could contribute to worldwide suitable waste management for the fertilizer industry. Graphical abstract: Image 1 Highlights: Highly polluted phosphogypsum leachates were effectively treated with DAS technology. The MgO-DAS and Ca(OH)2 -DAS removed around 100% of PO4, F, Fe, Zn, Al, Cd, U and As. The hazardousness of DAS wastes was depth-dependent according to the EU legislation. A low mobility of Cd and As was found in wastes upon different weathering scenarios. Solids from DAS systems could be considered a secondary source of P and calcite.